The Evaluation Of Universal Child Immunization (UCI) Management In The Work Area Of Bah Kapul Health Center, Siantar Sitalasari District In 2023 - Christo Khu; Dealita Khairani Daulay; Balqis Nurmauli Damanik (International Journal of Medicine and Health, 2024)
Background: Immunization is the governments promise to get Sustainable Development Goals (SDGs), especially to decrease the number of infant death rates. Universal Child Immunization (UCI) is an indicator of success in basic immunization in babies immune against a disease. Purpose: To analyze the process of management in achieving UCI. Research Methods: The research used qualitative phenomenological methods. The objective of the research was to analyze the process of management in achieving UCI. The research used qualitative phenomenological methods. It was done in the working area of Bah Kapul Puskesmas. The data were gathered by conducting in-depth interviews with 8 Informantts from Surveillance and Immunization Section Head, the Heads of Puskesmas, participants of immunization program, and practice midwife. Result : The result of the research showed that human resources were inadequate since their qualification was not in accordance with the standards, training was only done by the participants, facility and infrastructure such as KMS preparation and the facility outside the building were inadequate, lacked of staff cars for immunization personnel, there was no counseling about immunization in the field, people were not interested in the program, there were ignorance and lack of involvement of cross-sectors, and there was no monitoring from the Heads of Puskesmas for immunization outside the building. Conclusion : The Heads of Puskesmas should monitor directly immunization service outside the building and not only monitor through the report. The management of Puskesmas should provide counseling about the importance of immunization for targeted parents before posyandu service is done. The cross-sectors should support the implementation of immunization, actively play and collaborate in its implementation.